On-line Pachymetry Outcome of Ablation in Aberration Free Mode TransPRK. Issue 4 (July 2014) - Adib-Moghaddam, Soheil; Arba-Mosquera, Samuel; Salmanian, Bahram; Omidvari, Amir-Houshang; Noorizadeh, Farsad
Purpose: There are many independent factors that influence the outcome of refractive surgeries, consisting of patient characteristics and environmental factors. We studied the accuracy of central ablation depth compared to online pachymetry results. Methods: A total of 153 eyes that underwent TransPRK at Bina Eye Hospital, Tehran, Iran, were evaluated from November 2010 to January 2012 in a retrospective cross-sectional study. The relevant data were registered and bivariate correlations and linear regression association were investigated statistically. Results: The mean age was 29 ± 5 years. Distribution of refractive errors was as follows: compound myopic astigmatism 123 (80.4%), simple myopia 24 (15.7%), and mixed astigmatism 6 (3.9%). Mean ambient temperature and humidity levels intraoperatively were 23.49 ± 1.16°C and 28.91 ± 6.16%, respectively. There was a significant difference (p<0.001) between the preassumed central ablation depth (131.68 ± 32.72 μm) and the net level of ablation depth (measured by online pachymetry, 168.04 ± 41.47 μm). Temperature and humidity levels were not in any statistically significant correlation with the net amount of difference found. The backward linear regression was done to reveal the association between ablation depth and several variables. Conclusions: This study showed that there is deviation in optical coherence pachymetry online measurements done with SCHWIND AMARIS laser. Ambient temperature and humidity levels intraoperatively do not influence the outcome. However, basic structural characteristics of patients along with change in refractive index and corneal shrinkage because of corneal dehydration are associated with the differences.